Students’ Misconception on Algebraic Function Limits - Roma Suganda Batu Bara; Fitriani Hasibuan; Rama Nida Siregar ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Understanding the concept of limits is fundamental in calculus learning, yet many secondary school students continue to experience persistent conceptual difficulties. These difficulties often manifest as misconceptions that hinder students’ ability to connect algebraic representations, symbolic meanings, and underlying theoretical ideas in limits of algebraic functions. This study aims to analyze the types of misconceptions experienced by twelfth-grade students in learning the limits of algebraic functions. A qualitative descriptive approach was employed to obtain an in-depth understanding of students’ misconceptions. Data were collected using essay-type test items specifically designed to reveal misconceptions related to limits, followed by semi-structured interviews to confirm students’ reasoning and clarify their conceptual understanding. The data analysis followed three systematic stages: data reduction by distinguishing correct and incorrect responses, data display by categorizing incorrect responses into specific misconception types or unanswered items, and conclusion drawing based on recurring characteristics of the identified misconceptions. The results indicate that students experienced various types of misconceptions, including correlational, theoretical, systematic, basic, computational, and language-interpretation misconceptions. A total of 30% of misconceptions occurred in Item 1, no misconceptions were identified in Item 2, and 7% of misconceptions appeared in Item 3. These misconceptions were primarily related to students’ inability to connect relevant concepts, misunderstand the existence of limits, apply inappropriate procedures, and misinterpret mathematical symbols or problem statements. In conclusion, the findings emphasize the importance of instructional approaches that explicitly address conceptual understanding and symbolic interpretation to reduce misconceptions in learning the limits of algebraic functions.